A breath of fresh air. Issue 2 (15th February 2022) - Head, Steve
Abstract : Asthma management has advanced greatly since the 50s, 60s and 70s, when it was common for patients and healthcare professionals to adopt a more experimental approach, recalls Dr Steve Head.